2022
DOI: 10.1123/jmpb.2021-0062
|View full text |Cite
|
Sign up to set email alerts
|

CHAP-Adult: A Reliable and Valid Algorithm to Classify Sitting and Measure Sitting Patterns Using Data From Hip-Worn Accelerometers in Adults Aged 35+

Abstract: Background: Hip-worn accelerometers are commonly used, but data processed using the 100 counts per minute cut point do not accurately measure sitting patterns. We developed and validated a model to accurately classify sitting and sitting patterns using hip-worn accelerometer data from a wide age range of older adults. Methods: Deep learning models were trained with 30-Hz triaxial hip-worn accelerometer data as inputs and activPAL sitting/nonsitting events as ground truth. Data from 981 adults aged 35–99 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Event files from the activPAL were extracted via the CREA classification algorithm (version 8; PALanalysis), which was set to require ≥4 second for a new posture to be registered and generated sleeping time for removal from analysis. Minutes spent in various sedentary behaviors (ie, sitting, standing, sit to stand transitions, and stepping time) were derived from continuously recorded data [ 38 , 39 ]. The activPAL has been validated with good reliability and validity [ 40 - 42 ] for measuring sedentary behavior and stepping pattern in community-dwelling older adults [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Event files from the activPAL were extracted via the CREA classification algorithm (version 8; PALanalysis), which was set to require ≥4 second for a new posture to be registered and generated sleeping time for removal from analysis. Minutes spent in various sedentary behaviors (ie, sitting, standing, sit to stand transitions, and stepping time) were derived from continuously recorded data [ 38 , 39 ]. The activPAL has been validated with good reliability and validity [ 40 - 42 ] for measuring sedentary behavior and stepping pattern in community-dwelling older adults [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…RenderX [38,39]. The activPAL has been validated with good reliability and validity [40][41][42] for measuring sedentary behavior and stepping pattern in community-dwelling older adults [43].…”
Section: Xsl • Fomentioning
confidence: 99%
“…The recent developments in the field of hip-worn accelerometer algorithms have made it possible to quantify SB as per the proper definition. Both the angle for postural estimation (APE) method [20] and convolutional neural network hip accelerometer posture (CHAP) method have shown over 90% accuracy in classifying body postures [21,22]. The APE method is based on two concepts: the Earth's gravity vector is constant, and the body posture during walking is upright.…”
Section: Introductionmentioning
confidence: 99%
“…Chastin et al concluded recently that the data from hip-worn accelerometry can provide accurate and meaningful estimates of PA [2]. Further, recent advances in data analysis have made it possible to quantify also the sedentary time spent in standing, sitting, and reclining postures [3,4].…”
Section: Introductionmentioning
confidence: 99%